Aesthetics Skylines in Manado - Desty Rara Retna Kalude,; Djubir Ruslan Eddy Kembuan,; Keith Francis Ratumbuisang, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The impact of urban development is a change in the face of the city, with various building functions and heights building so that create its skyline Alone. City Manado showing exists growth city in a manner physique and non-physical so that the City of Manado has unknowingly changed the face of the city, especially in the regions Coast. Changes in the face of the city of Manado in the coastal area include changes to the skyline which was originally flat become more expressive when compared to other areas in the city of Manado. The city skyline can be an overview of what is most valued in a city, other than that the beauty of the skyline can only be enjoyed from long distance. Skyline beauty depends on observer perception and the physical form of the city. Research objectives namely to analyze the aesthetic quality of the skyline in the waterfront area of the city of Manado and analyze what factors are there Which shape it. Study This use method qualitative with approach descriptive analysis. The data analysis approach was carried out in a qualitative descriptive manner with the stages of segment division, analysis of the results recording, ground check and analysis of visual element variables. The results showed that: of the seven variables physique skyline aesthetic, only exists five variable which are contained on location study.